From Being to Becoming: An International Student’s Journey at Becoming an International Education Scholar - Castiello-Gutiérrez, Santiago (Journal of International Students, 2022)
Framed as a critical autoethnography (Boylorn & Orbe, 2020), this study is a reflection on my personal and academic journey from ‘being’ an international student in the United States, to ‘becoming’ a scholar who studies issues of international student mobility. Through a comprehensive dataset comprised of self-reflection, personal communications, published and unpublished scholarly works, and presentations, I show how by being the Other and observing or experiencing issues of discrimination against international students, I transformed my scholarly identity and used my agency to bring attention to these issues.